2022
DOI: 10.1017/s0022215122002419
|View full text |Cite
|
Sign up to set email alerts
|

Should mild obstructive sleep apnoea be treated? A systematic review from the standpoint of disease progression

Abstract: Objective This study was a systematic review to investigate the progression of untreated obstructive sleep apnoea in order to evaluate whether mild obstructive sleep apnoea should be treated from the standpoint of disease progression. Method The database search study outcomes that were collected included Apnea Hypopnea Index and Respiratory Disturbance Index. A meta-analysis of obstructive sleep apnoea severity over time intervals was performed. Results A total of 17 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…3 Additionally, Fong et al . 2 found that predictors for disease progression in mild obstructive sleep apnoea are: age of less than 60 years and a baseline body mass index of less than 25 kg/m 2 .…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…3 Additionally, Fong et al . 2 found that predictors for disease progression in mild obstructive sleep apnoea are: age of less than 60 years and a baseline body mass index of less than 25 kg/m 2 .…”
mentioning
confidence: 98%
“…The authors found that although untreated mild OSA does show a gradual increase in the Apnoea Hypopnea Index, or Respiratory Disturbance Index, over 53.1 months, this rate of increase slowly plateaus, and does not progress across categories into moderate, or severe, OSA. 2 The authors therefore conclude that it is difficult to justify the treatment of mild OSA from the standpoint of disease progression. A study published last year also confirmed at the molecular level less severe airway inflammation in mild OSA patients compared with moderate to severe OSA.…”
mentioning
confidence: 99%
See 2 more Smart Citations